Faith and Bayan: Evangelical Christian Engagement in the Philippine Context : (Book Review) - Samdao, Francis (Asia journal of theology, 2023)
This is a book review of Lorenzo C. Bautista, Aldrin M. Peñamora, and Federico G. Villanueva, eds., Faith and Bayan: Evangelical Christian Engagement in the Philippine Context (Carlisle, UK: Langham Global Library, 2022), xiii + 183 pp., £13.99, ISBN 978-1-83973-277-5, paperback.